Development Of Android-Based Digital Maps for Learning the Mapking Process - Rusli, Mulyadi; Purnama, Fery; Latief, Suryawahyuni; Susanto, Darex; Megawati, Merty; Adriana, Windy (Information Technology and Science (ITScience), 2023)
Educational media is an important component in education for making the Jambi Province Map which must be presented in an innovative way. Media that is currently known is a digital map that is not easy to read and the position and location or color errors, this situation will lead to errors in meaning and purpose. This study aims to make a product in the form of a digital map and test its validity based on media experts. This study uses the ADDIE model development procedure which is modified into 4 stages, namely analysis, design, development and implementation. The Likert scale method was used as an analysis to retrieve information from 20 class VII students of SMPN I Jambi City as respondents, while the validation method was used as an analysis to test product validity. The results of the development in this study are in the form of digital map images designed through the Android-based UMapper and WhatsApp Plus Aero applications. Test results from two material experts show that this product gets a score of 47 and 46 out of a maximum score of 50 which means very good. This shows that the development of this media is very good in meeting the needs of students in the field of education for making Jambi Province maps, being creative and innovating in using media in the form of android-based applications.